Action of the myotoxin from Bothrops brazili Hoge, 1953 snake venom (Ophidia: Viperidae) - Pantigoso, Carmen (2002)
The myotoxin isolated from the venom of the snake Bothrops brazili has been studied in its mode of action. In the first hour of activity the myotoxin injected in the gastrocnemius muscle of white mice, induces the release of creatine kinase and lactate dehydrogenase, while by PAGE-SDS, it is shown that the incubation of miotoxin with isolated gastrocnemius muscle releases other proteins from this tissue. Moreover myotoxin produces hipercontraction, delta lesions and increases the concentration of intramuscular calcium “in vivo” and “in vitro”, which does not depend on extracellular calcium entry through dyhidropyridine receptors. This increase of calcium would explain the hipercontraction observed. Also it could trigger the activation of endogenous proteases and lipases, which would lead to muscle necrosis.